Considering the methodological limitations in the evidence base of antidepressants for depression: a reanalysis of a network meta-analysis - Munkholm, Klaus (BMJ Open, 2019)
OBJECTIVES: To investigate whether the conclusion of a recent systematic review and network meta-analysis (Cipriani et al) that antidepressants are more efficacious than placebo for adult depression was supported by the evidence. DESIGN: Reanalysis of a systematic review, with meta-analyses. DATA SOURCES: 522 trials (116 477 participants) as reported in the systematic review by Cipriani et al and clinical study reports for 19 of these trials. ANALYSIS: We used the Cochrane Handbook’s risk of bias tool and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to evaluate the risk of bias and the certainty of evidence, respectively. The impact of several study characteristics and publication status was estimated using pairwise subgroup meta-analyses. RESULTS: Several methodological limitations in the evidence base of antidepressants were either unrecognised or underestimated in the systematic review by Cipriani et al. The effect size for antidepressants versus placebo on investigator-rated depression symptom scales was higher in trials with a ‘placebo run-in’ study design compared with trials without a placebo run-in design (p=0.05). The effect size of antidepressants was higher in published trials compared with unpublished trials (p<0.0001). The outcome data reported by Cipriani et al differed from the clinical study reports in 12 (63%) of 19 trials. The certainty of the evidence for the placebo-controlled comparisons should be very low according to GRADE due to a high risk of bias, indirectness of the evidence and publication bias. The mean difference between antidepressants and placebo on the 17-item Hamilton depression rating scale (range 0–52 points) was 1.97 points (95% CI 1.74 to 2.21). CONCLUSIONS: The evidence does not support definitive conclusions regarding the benefits of antidepressants for depression in adults. It is unclear whether antidepressants are more efficacious than placebo.